Study on health and behavioural problems of adolescents - a school based intervention program - Hanafiah,M.S.,; Khadijah, S.,; Md. Idris,M.N.,; Kasmini, K., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2000)
﻿The process of urbanisation in Malaysia has lead to more mothers joining the working force as there are more jobs available (1). Studies show that increase in women’s participation in the work force correlates with increase in divorce rates (2). The breaking up of immediate family as well as the dwindling of extended family structure (3), leading to a more nucleated family are responsible to a significant extent for the present high magnitude of neglected adolescents (2). Adolescent boys and girls grow and develop without adequate love and guidance that they desperately require (4). Dysfunctions within the family and academic pressure from school-life are among the push factors for adolescent negative behaviour (5). At the same time, adolescents boys and girls are lured toward negative behaviour by environmental factors [pull factors] (6) such as the mass media and peer pressure , which resulted in an increase of juvenile delinquency, “bohsia” practices, out of wedlock pregnancy, prostitution, induced abortion, smoking, drug addiction and other negative activities (6). About 10 - 20% of adolescents experience psychosocial problems. They also lack adequate religious upbringing and “living skills” required to deal with problems of everyday life (4). There are a variety of programmes (7) which have been formulated to counter these problems but their focus has been symptomatic in nature and are not grassroot oriented nor cost effective. We believe that preventive (7) programmes (8,9) would be more suitable and effective for combating these issues. This project has been developed to identify adolescents with health and behavioural problems or are at high risk of such problems and to carry out comprehensive school- based prevention strategies starting from as early age as possible.